Cognitive Acceleration in Mathematics Education in Tonga: Effects on students’ mathematics achievement, motivation, and self-regulation - Finau, Teukava (Curtin University, 2017)
To address the issue of Tongan secondary students’ poor performance in mathematics, this study implemented an innovative teaching approach called Cognitive Acceleration in Mathematics Education (CAME) program, and evaluated its effects on students’ mathematics achievement, motivation, and self-regulation. The results from this quasi-experimental study indicate that the students who learnt through the CAME program improved their performance substantially compared to their counterparts. This findings encapsulated the CAME as possible solution for improving students’ mathematics performance.